Improved age estimates for key Late Quaternary European tephra horizons in the RESET lattice - Bronk Ramsey, C; Alert, P; Blockley, S; Hardiman, M; Housley, R; Lane, C; Lee, S; Matthews, I; Smith, V; Lowe, J (Elsevier, 2015)
The research project 'Response of Humans to Abrupt Environmental Transitions' (RESET) used tephra layers to tie together and synchronise the chronologies of stratigraphic records at archaeological and environmental sites. With the increasing importance of tephra as chronological markers in sedimentary sequences, both in this project and more generally, comes a requirement to have good estimates for the absolute age of these volcanic horizons. This paper summarises the chronology of the key tephra in the RESET tephra lattice in the time range 10-60 ka BP, from the existing literature, from papers produced as part of the RESET project, and reanalysis conducted for this paper. The paper outlines the chronological ap- proach taken to the dating of tephra within the RESET project, and the basis for further work, as part of the INTIMATE (INTegrating Ice core MArine and TEr- restrial records) initiative. For each of the tephra layers in the lattice, the existing literature is discussed and, where relevant date estimates updated using the latest radiocarbon calibration curves (IntCal13 and Marine13) and methods. Maps show the approximate extent of tephra finds, giving a visual indication of the coverage of the lattice in different time-periods.